2007
DOI: 10.1080/14992020601014979
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of NRT and behavioral measures for MAPping elderly cochlear implant users

Abstract: We investigated the acceptability of electrophysiologically derived MAPs and the effect of these MAPs on speech perception in elderly adults using Nucleus 24 cochlear implants. Eight implant recipients aged 75 years or older trialed an electrophysiologically derived MAP and a behavioral MAP. The electrophysiologically derived MAP was based on the threshold and maximum comfort level for electrode 10 and evoked compound action potential thresholds measured on six electrodes using neural response telemetry (NRT).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…Several studies have reported higher thresholds and smaller ECAP amplitudes in the basal electrodes than in the apical electrodes [29,36,38,43,60]. The dominant paradigm to explain these findings has been that there is a smaller number of preserved vital neurons in the basal part of the cochlea, which is consistent with postmortem pathohistological studies of the temporal bones [9,17,29,33,38,43,46].…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Several studies have reported higher thresholds and smaller ECAP amplitudes in the basal electrodes than in the apical electrodes [29,36,38,43,60]. The dominant paradigm to explain these findings has been that there is a smaller number of preserved vital neurons in the basal part of the cochlea, which is consistent with postmortem pathohistological studies of the temporal bones [9,17,29,33,38,43,46].…”
Section: Discussionsupporting
confidence: 53%
“…The dominant paradigm to explain these findings has been that there is a smaller number of preserved vital neurons in the basal part of the cochlea, which is consistent with postmortem pathohistological studies of the temporal bones [9,17,29,33,38,43,46]. An alternative explanation is that the electrode array in the basal part of the cochlea is more distant from SGC or that there is a higher risk for surgical trauma in that part of the cochlea [29,60]. Furthermore, several studies have reported variability in the ECAP thresholds, amplitudes, morphologies, and MAP levels along the array, indicating that the spatial distribution of neuronal populations stimulated by a particular electrode is heterogeneous [24,38].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Hughes et al, 2000; Mason et al, 2001; Gordon et al, 2002; Kaplan-Neeman et al, 2004) as well as the elderly (e.g. Pedley et al, 2007). …”
mentioning
confidence: 99%
“…Results from intraoperative electrophysiological testing such as neural response telemetry (NRT) and electrical auditory brainstem response (EABR) have been reported as possible indicators of post-operative outcomes with children (King et al, 2006) and adults including the elderly (Pedley et al, 2007). Poor morphology (defi ned as the absence of one or more waveforms, poorly formed waves or delayed waves) of the intra-operative EABR could indicate that the recipient will have some diffi culty integrating the signal from their cochlear implant, particularly initially.…”
Section: Introductionmentioning
confidence: 99%